From Risk to Resilience: A Data-Driven Mediation Analysis of Supply Chain Risk Management and Firm Performance in Chinese Manufacturing - Lei, Mingyu; Zakuan, Norhayati; Hasan, Mohd Zulfabli; Mat Saman, Muhamad Zameri; Chen, Xin (Digital Technologies Research and Applications, 2026)
This paper investigates whether supply chain resilience serves as a mediator in the relationship between supply chain risk management and firm performance in China’s manufacturing industry, leveraging big data analytics and digital technologies to fill the theoretical void on how risk management practices contribute to financial performance in the digital era. Applying resource-based theory and dynamic capabilities theory approaches to guide theory development constructs an integrated framework in which supply chain resilience serves as the key conduit or mediation variable that translates diversified strategies to better organizational effectiveness. Using panel data from 347 Chinese A-share listed manufacturing firms (2,418 firm-years, 2015–2023) drawn from the China Stock Market and Accounting Research (CSMAR) database, this study employs panel regression and bootstrap mediation analysis to test the proposed framework. Supply chain risk management is operationalized through supplier and customer diversification, while supply chain resilience is captured by financial slack, operational efficiency, supply chain redundancy, and relationship stability. Results from panel regression and bootstrap mediation analysis confirm that supply chain risk management significantly enhances firm performance, with supply chain resilience serving as a significant partial mediator that substantially channels the effect. The findings are robust across alternative variable specifications, lagged models, and winsorized samples. The findings suggest that building supply chain resilience is the primary channel through which risk management investments translate into improved financial performance.